High-pressure liquid chromatographic analysis for identification of in vitro and in vivo metabolites of 4-phenethyl-5-[4-(1-(2-hydroxyethyl)-3,5dimethyl-4-pyrazolylazo)phenyl]-2,4-dihydro-3H-1,2,4-triazole-3-thione in rats - KABASAKAL, LEVENT (ELSEVIER SCIENCE BV, 2006)
All azo colorants whose metabolism can liberate a carcinogenic arylamine, are suspected of having carcinogenic potential. Therefore, a new azo compound 4-phenethyl-5-[4-(1-(2-hydroxyethyl)-3,5-dimethyl-4-pyrazolylazo)phenyl]-2,4-dihydro-3H-1,2,4-triazole-3-thione (substrate) was prepared to investigate its in vitro and in vivo biotransformation in rats by HPLC. Chromatographic separation of substrate and its metabolites was performed using a Chromasil C-18 column. The mobile phase consisted of acetonitrile and water in a linear gradient system. From the biotransformation of this compound, the reduction metabolite 4-(2-phenethyl)-5-(4-aminophenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione was identified by comparing it to reference standard by HPLC-DAD. In the in vivo study, identification of the unknown peak which was the N-acetylation metabolite was confirmed by LC-MS spectrometry. Besides this, the azo compound was reduced to its corresponding amine in intestinal and cytosolic parts. In addition, oxidation of the methyl group and the phenyl ring, and reduction of azo group to hydrazo were identified in the cytosolic part using LC-MS. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: azo; metabolism; HPLC; AZO-DYE; FOOD DYES; DERIVATIVES; MUTAGENICITY; REDUCTION; ASSAY